One new species of the genus Calamus L. (Arecaceae Schultz-sch.) for the flora of Vietnam - Anh, Tran Phuong; Khoi, Nguyen Khac (Academia Journal of Biology, 2014)
The genus Calamus L. (Arecaceae Schultz.-Sch.) has 370 species in the world, with wide distribution from the tropics of Africa, India, China to Australia. There are 18 species and one variety in Vietnam. During the study, we have found one species as new record (Calamus acanthospathus Griff.) for the flora of Vietnam. This species can be recognized by: climbing, solitary, flagellate; knee present; sheath has many needle-like spines, short bristly ocrea; leaflets regular, boat-shape (7-11 cm length, 3-3,5 cm wide); terminal of the rachis is one leaflet; female inflorescence flagellate, stiff, erect; primary bracts entire. This species closes to Calamus bousigonii Becc. but differ by: veins finish at the top; leaflets boat-shape; inflorescence short, erect; rachilla shorter. This species was collected in the Xuanson national park, Phu Tho province.